³¹P magnetization transfer magnetic resonance spectroscopy: assessing the activation induced change in cerebral ATP metabolic rates at 3 T - Chen, Chen; Stephenson, Mary C.; Peters, Andrew; Morris, Peter G.; Francis, Susan T.; Gowland, Penny A. (Wiley, 2017)
Purpose: In vivo ³¹P MRS magnetization transfer (MT) provides a direct measure of neuronal activity at the metabolic level. This work aims to use functional ³¹P MRS-MT to investigate the change in cerebral ATP metabolic rates in healthy adults upon repeated visual stimuli.